Idiopathic Bilateral Profound Hypotony in an Unknown Progressive Neurodegenerative Disorder. Issue 5 (May 2017) - Provencher, Lorraine M.; Carter, Pamela C.; Alward, Wallace L.M.
Abstract : Purpose: To present a unique case of idiopathic bilateral hypotony in a patient with progressive, undiagnosed neurological decline, possibly due to mitochondrial disease, and to explore mechanisms of disease and potential treatment options. Methods: This is a case report. Patient: A 17-year-old boy with a history of chronic progressive bilateral vision loss and hypotony in the setting of progressive gait abnormalities, lower extremity spasticity, nystagmus, and urinary retention starting around age 8. Despite extensive biochemical and genetic evaluation, no systemic etiology has been identified. He had no history of ocular trauma or surgery. Results: Examination confirmed the above history as well as decreased vision, significant bilateral astigmatism (7 D), short axial-eye-lengths, and disc edema with chorioretinal folds in the left eye. There was no inflammation or ciliary body detachment. We propose the etiology is similar to hypotony in myotonic dystrophy, in which low intraocular pressure may result from aqueous egress across the ciliary body face. The best treatment remains unclear, but surgical closure of the iridocorneal angle is under careful consideration. This may halt nonconventional (suprachoroidal) outflow. Conclusions: Management of ocular hypotony is typically directed at the underlying etiology. Idiopathic hypotony poses a unique treatment challenge. If excess aqueous flow across the ciliary body face is responsible, intentional closure of the iridocorneal angle may preserve vision. Abstract : Supplemental Digital Content is available in the text.